'Sewing in the Next World': Mary Hays as Dissenting Autodidact in the 1780s - Walker, Gina (Romanticism on the Net)

(untitled) (Université de Montréal, 2002)
AbstractMary Hays believed that "in the intellectual advancement of women […] is to be traced the progress of civilization." This essay traces the trajectory of Hays's own "advancement," focusing on Robert Robinson's tutelage from 1781 to her initial encounters with Wollstonecraft. The rational culture of late-eighteenth-century radical Dissent encouraged Hays to venture into the masculine strongholds of Enlightenment understanding, but here, as in the larger world, the "insuperable barriers" of gender obtained. Despite these obstacles, Hays forged an identity as female autodidact in the 1780s, readying herself to embrace Wollstonecraft's "revolution in female manners." Hays's initial contribution was to urge a new cognitive freedom, the recognition that women, too, may aspire to "the emancipated mind [which] is impatient of imposition, nor can it, in a retrogade [sic] course, unlearn what it has learned, or unknow what it has known." Hays's unfinished transition from sheltered puritan to Nonconformist apprentice to ardent feminist provides the missing link in our appreciation of her collaboration with Wollstonecraft and Godwin in the 1790s. I show how Hays was transformed into the obvious candidate for public denunciation as chief living "unsex'd female" in Wollstonecraft's stead.